ASIF in Poland in the light of national budget expenditure since 1991. Justification functioning system separateness among the EU countries = KRUS w Polsce w świetle krajowych wydatków budżetowych po 1991 r. Uzasadnienie funkcjonowania odrębności systemu wśród krajów UE - Czyżewski, Andrzej; Matuszczak, Anna (Zielona Góra: Faculty of Economics and Management Press)
The purpose of this article was to show that the existence of ASIF, as an important element of the social insurance system for farmers in Poland is not unique on a European scale. There were shown relationships ASIF with the budget and the characteristics of social insurance of farmers in selected countries of the European Network of Agricultural Social Protection Systems (ENASP).
Keywords: budżet rolny; wydatki budżetowe; ubezpieczenia społeczne; KRUS; agricultural budget; budget expenditures; social security; ASIF